The Assessment of Stormwater Management and Drainage Master Plan: Sepang, Malaysia and Surakarta, Indonesia - Roslan, Eriza Najwa (2022)
The population of citizens continues to rise each year in Malaysia and Indonesia. In order to ensure that they can fulfill their needs, the growth of the human population has significantly increased development. Rapid growth is one of the elements that will cause flooding since the ability of the soil to store water is declining. On the other hand, flooding is happening when the capacity of the river is insufficient to cater rainfall during heavy rain which caused river water to overflow surrounding dry land that is near to the river or pond.